High diagnostic yield of electromagnetic navigation bronchoscopy performed under cone beam CT guidance: results of a randomized Belgian monocentric study - Bondue, Benjamin; Taton, Olivier; Tannouri, Fadi; Van de Velde, Nikita; Remmelink, Myriam; Leduc, Dimitri (BMC pulmonary medicine, 2023)
With the increasing use of low dose CT scans, numerous pulmonary nodules are detected. As majority of them are benign, development of efficient non-surgical diagnostic intervention is mandatory. Electromagnetic navigation bronchoscopy (ENB) has been developed to reach difficult to access lesions. The aim of the present study was to compare the diagnostic yield of ENB procedures performed in a classical endoscopy suite or in a hybrid room equipped by a cone beam CT (CBCT). A monocentric randomized study was performed in the Erasme Hospital between January 2020 and December 2021. Lung nodules of maximum 30 mm of diameter were eligible. In both arms (endoscopy or CBCT suites), ENB, fluoroscopic guidance and a radial endobronchial ultrasound were used to reach the lesion. Then six trans-bronchial biopsies (TBB) and one trans-bronchial lung cryobiopsy (TBLC) were performed. Primary outcomes were the diagnostic yield and diagnostic accuracy of the procedure. Forty-nine patients were randomized (24 in the endoscopy and 25 in the CBCT arms). The lesion size was 15,9 ± 4,6 mm and 16,6 ± 6,0 mm respectively (mean ± SD, p = NS). The diagnostic yield of ENB performed under CBCT guidance was 80% compared to 42% when performed in the endoscopy suite under standard fluoroscopic guidance (p < 0,05). Similarly, the diagnostic accuracy in the CBCT group was 87% compared to 54% for the endoscopy group (p < 0,05). Duration of the procedure in the CBCT and endoscopy arms was 80 ± 23 and 61 ± 13 min respectively (mean ± SD, p < 0,01). Performing TBLC in addition to TBB increased the diagnostic yield by 14% (17 and 12,5% in CBCT and endoscopy suites respectively, p = NS). This study highlighted the additional value to perform ENB procedure under CBCT guidance for small size (less than 2 cm of diameter) pulmonary nodules. Clinical trial registration number: NCT05257382.